Connecting english with environmental education - Armijos G., Jenny; López P., Tania
The teaching of the English language is limited to the instruction of grammar and basic vocabulary; teachers put emphasis on memorization and mechanical repetition. Also, discussion of themes without interest for the student is an evident problem in the class. Moreover, English is isolated from the rest of the subjects. For these reasons, we consider necessary to link English with other subjects such as Environmental Education, using English as a tool to create micro-projects with themes focused on nature. So that we planned to establish a project of educational intervention for the 10th grade in San Juan de Jerusalén School.